2017
DOI: 10.1007/s10433-017-0427-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of maltreatment of people with dementia in Spain: usefulness of the Caregiver Abuse Screen (CASE)

Abstract: The objective of our study is to validate the Caregiver Abuse Screen (CASE) as an instrument for detecting the maltreatment of people with dementia in Spain. In total, 326 informal caregivers of people with different types of dementia were interviewed in several cities in northwest Spain. The caregivers were selected from outpatient neurology clinics and associations of relatives of people with Alzheimer's disease and other dementias. A comprehensive sociodemographic questionnaire was administered to all parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
1
17
1
Order By: Relevance
“…However, 2 studies of validation have shown that the CASE has adequate psychometric properties to detect risk of abuse in Spanish elders with dementia. 25,46 Second, the CASE emphasizes physical items (excluding emotional or financial forms), and no external resources (eg, hospital records) were available to corroborate the ARB. However, CASE is a well-recognized tool, not only suggestive of different forms of abuse (interpersonal and neglect), but also indicative of stress that could lead to abusive behavior in the future.…”
Section: Burden As Mediator Factor Of the Relationship Between Socimentioning
confidence: 99%
See 3 more Smart Citations
“…However, 2 studies of validation have shown that the CASE has adequate psychometric properties to detect risk of abuse in Spanish elders with dementia. 25,46 Second, the CASE emphasizes physical items (excluding emotional or financial forms), and no external resources (eg, hospital records) were available to corroborate the ARB. However, CASE is a well-recognized tool, not only suggestive of different forms of abuse (interpersonal and neglect), but also indicative of stress that could lead to abusive behavior in the future.…”
Section: Burden As Mediator Factor Of the Relationship Between Socimentioning
confidence: 99%
“…However, CASE is a well-recognized tool, not only suggestive of different forms of abuse (interpersonal and neglect), but also indicative of stress that could lead to abusive behavior in the future. 24,46 Besides, detection of abuse, a hidden phenomenon, remains a challenge itself, and there is no established gold standard for detection.…”
Section: Burden As Mediator Factor Of the Relationship Between Socimentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic stress has a negative effect on the caregiver's mental and perceived health (depression, anxiety, psychosomatic and immunological disorders, cardiovascular problems...) and increases the risk of chronic health problems (heart disease, high blood pressure…) and the development of new diseases. In addition, the stress and emotional distress of caregivers has serious consequences for them, in particular their progressive inability to fulfill their role as caregivers, resulting in early institutionalization or unplanned hospitalization of the old person (9) and the risk of abuse or mistreatment for the care recipient, particularly those with dementia and or disruptive behavioral symptoms (10)(11)(12)(13)(14). Because of these consequences for caregivers and at a second level for the care recipient, it is necessary to introduce interventions and support for the caregiver (3,(15)(16)(17).…”
mentioning
confidence: 99%